(untitled) - Bartlett, Bruce (Amsterdam, 2007)
From planning on paper to the practical aspects of the set up, this book offers you expert advice on every stage of recording on location. Polish your skills for recording surround sound by following the written and audio examples of different miking techniques.
Keywords: Sound,Âm thanh; Recording and reproducing,Ghi và tái tạo; Cẩm nang, hướng dẫn .v.v...